Un dialogo possibile? Teoria delle organizzazioni e studio dei partiti - Pizzimenti, Eugenio (SocietàMutamentoPolitica, 2023)
Literature devoted to party organizations rarely relies on Organization Theory. With the exception of the fundamental contribution by Panebianco, which dates back to 1982, limited efforts have been made towards a mutual contamination between the study of party organizational development and the vast body of theories, approaches and analytical frameworks that crowd Organization Theory. Moreover, while Organization Theory has recently paid attention to the study of political parties, party scholars are still committed to accumulating empirical knowledge or, at best, elaborating ideal-typical models. The aim of this contribution is to favour a cross-fertilization between these two literatures, by building on the premises of organizational institutionalism and on the organizations as multi-dimensional rational open systems perspective. Despite our effort is primarily conceptual, our arguments are conceived to be properly translated into empirical observations.